A Convenient, Mild, and Green Synthesis of NH‐Sulfoximines in Flow Reactors. Issue 44 (5th September 2017) - Degennaro, Leonardo; Tota, Arianna; De Angelis, Sonia; Andresini, Michael; Cardellicchio, Cosimo; Capozzi, Maria Annunziata; Romanazzi, Giuseppe; Luisi, Renzo
Abstract : NH‐sulfoximines are emerging as useful and important targets in drug discovery and synthetic organic chemistry. We report herein the development of an efficient, convenient, and sustainable continuous‐flow strategy, for the direct, straightforward preparation of NH‐sulfoximines by using sulfides or sulfoxides as suitable starting material. The flow process uses PhI(OAc)2 as the oxidant and aqueous solutions of ammonia as the N source. The scope of the reaction has been demonstrated by using several substituted sulfides and sulfoxides including enantioenriched and biologically relevant starting materials. The flow strategy was found to be more convenient with respect to conventional batch processing. Abstract : We report herein the development of an efficient, convenient, and sustainable continuous‐flow strategy for the direct, straightforward preparation of NH‐sulfoximines starting either from sulfides or from sulfoxides. The flow process uses PhI(OAc)2 as the oxidant and aqueous solutions of ammonia as the N source. The flow strategy was found to be more convenient than the conventional batch processing.